Diversity Tree Varieties Mango (Mangifera indica L.) in Critical Areas - Zulfikar Zulfikar; Achmad Kholiilur Rohman (LPPM Universitas KH. A. Wahab Hasbullah, 2021)
Critical land is often a problem in various regions in Indonesia, especially in the Jombang district. Various efforts have been made by the community in tackling the critical land they face. One of them is by cultivating mango trees. In the Jombang district, there are quite a lot of mango trees with various varieties. This study aims to determine the diversity and dominance of mango varieties growing on critical land in Plandaan District, Jombang Regency. This research was conducted by purposive sampling in 3 villages with a total sample of 30 yards/gardens, based on the availability of data and information in the field. This research was conducted using a quadratic transect method by determining the research location by purposive sampling with a plot size (20x20 m2). Data analysis was carried out qualitatively and quantitatively. Quantitative data analysis using vegetation analysis, namely: density (Kr), Frequency (Fr) Important Value Index (INP), Dominance (C), and Diversity Index (Ĥ). From the results of the study, it was found that 7 varieties of mango were planted by the community on critical land in the Plandaan District, the mango that was most widely cultivated by the community was the Gadung mango. The existence of other varieties of mango is only found in very small quantities and has begun to be abandoned by the community.